1979
DOI: 10.2134/jeq1979.00472425000800010010x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Gradients of Arsenic, Copper, and Chromium around Preservative‐Treated Wooden Stakes

Abstract: The distribution gradients of arsenic and chromium in soil around and below nominal 50‐ by 101‐mm (2‐ by 4‐in) southern pine stakes that were treated with either chromated copper arsenate (CCA Type I or Type II) or in ammoniacal copper arsenate (ACA) and exposed nearly 30 years in Poarch fine sandy loam soils in southern Mississippi indicate that the small amounts of As and Cr that move from the stakes into the soil are sorbed by the soil proximal to the stakes. The distribution gradient for copper about the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Lyytikäinen et al (2001) have reported the bioaccumulation of arsenic, but not chromium or copper, in worms (Lumbriculus variegatus) exposed to sawmill sediments containing residues of CCA. Lebow et al (1999) cited release rates of 0.007-0.032 µg cm −2 day −1 for chromium 0.17-0.95 µg cm DeGroot et al (1979) measured the distribution gradients of arsenic and chromium in fine sandy loam soil around and below CCA-treated southern pine stakes. From their measurements, they concluded that there was no significant contribution of arsenic or chromium to the surrounding soil or water.…”
Section: Production Of Cca-treated Building Timbermentioning
confidence: 99%
“…Lyytikäinen et al (2001) have reported the bioaccumulation of arsenic, but not chromium or copper, in worms (Lumbriculus variegatus) exposed to sawmill sediments containing residues of CCA. Lebow et al (1999) cited release rates of 0.007-0.032 µg cm −2 day −1 for chromium 0.17-0.95 µg cm DeGroot et al (1979) measured the distribution gradients of arsenic and chromium in fine sandy loam soil around and below CCA-treated southern pine stakes. From their measurements, they concluded that there was no significant contribution of arsenic or chromium to the surrounding soil or water.…”
Section: Production Of Cca-treated Building Timbermentioning
confidence: 99%
“…Tests of poles treated with pentachlorophenol in P9 Type‐A oil showed little evidence of preservative migration more than 300 mm from the poles (Muraka et al, 1996). Mortimer (1991) found little evidence of movement of metals from poles treated with CCA amended with polyethylene glycol, while other work noted substantial metal levels at the groundline immediately adjacent to CCA‐treated poles and treated stakes (Cooper et al, 2001; Cooper and Ung, 1997; DeGroot et al, 1979; Zagury et al, 2003); however, there is little information on the movement of metal components from ACZA‐treated wood.…”
mentioning
confidence: 99%
“…Studies of the movement of CCA constituents in soils generally agree that the constituents are not highly mobile, although some movement of arsenic may occur in sandy soils (De Groot et al 1979, Bergman 1983, Brown 1986, Bergholm and Dryler 1989, Bergholm 1990, Murphy and Dickinson 1990, Lund and Fobian 1991, Holland and Orsler 1995. Movement of both copper and chromium in soil is limited by their strong reactivity with organic soil components (Bergholm 1990, Lund andFobian 1991), while arsenic retention in soil is more influenced by the presence of iron, aluminum, and clay (Fordham andNorrish 1974, Frost andGriffin 1977).…”
Section: Soil Concentrationsmentioning
confidence: 99%